“OLAHAN KAWASAN KONSERVASI” DESA WISATA JAWA (MEWUJUDKAN MASYARAKAT SADAR WISATA BERBASIS POTENSI LOKALPADA MASYARAKAT KEJI, UNGARAN BARAT) - Fulia Aji Gustaman; Harto Wicaksono; Fajar Fajar (Prodi Sosiologi FISIP Universitas Teuku Umar, 2016)
Tourism event is new industrial activities that bring many economic benefits to the perpetrator and the owner of the area where the tourism activities take place, as the case that was occur in Keji Village community. Processed tourist villages based on community conservation Keji Village has a different potential with tourist activities in Indonesia. Tourism that is offered by Keji Village is a reproduction of socio-cultural and nature, combined with the needs of the tourists both local and foreign. In realizing Keji Village as a tourist center that sells the peculiarities of the village in a sustainable manner, Keji community has done a variety of strategies, including building participation of Keji Village community. Participation conducted by community still limited manipulative participation by the management. It was proven when integrating a range of potential activity and a series of typical tourist village still seem not communicated. Participation is still not reached an agreement in realizing the Keji Village as a tourist village. One of the indicators is internal conflict among the administrator, community, and art galleries in the Keji Village. Even though with the management system and marketing potential are being made to introduce to the outside world is still experiencing problems. Problems that occur because people are in a hurry to get maximum benefit economically. Such orientation makes people complacent, that in fact Keji Village community wants to offer the culture of rural communities that packed in the travel industry for the tourist. Keywords: conservation area, tourist village, and tourism awareness